2020
DOI: 10.1186/s40792-020-00984-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic benefit of conversion surgery for HER2 positive stage IV gastric cancer; a case series study of eleven patients treated with trastuzumab-based chemotherapy

Abstract: Background Since the ToGA trial, trastuzumab-based chemotherapy is the standard treatment for HER2 positive stage IV gastric cancer. However, it is not yet clear whether surgical resection after trastuzumab-based chemotherapy (conversion surgery) can improve survival of HER2 positive stage IV gastric cancer. The purpose of this study is to evaluate the prognostic benefit of conversion surgery in HER2 positive stage IV gastric cancer patients. Case p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Surprisingly, in the present study, the 5-year OS rate in the conversion surgery group with HER2-positive AGC was 68.6%. Hayano et al [ 18 ] examined prognostic data retrospectively in six patients with HER2-positive AGC, who underwent conversion surgery after trastuzumab-containing chemotherapy, and found that the 3-year survival rate was 66.7%. These findings imply that patients with HER2-positive AGC may be more suitable candidates for conversion surgery after trastuzumab-based chemotherapy, with greater improvements in prognosis, than those with HER2-negative AGC.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in the present study, the 5-year OS rate in the conversion surgery group with HER2-positive AGC was 68.6%. Hayano et al [ 18 ] examined prognostic data retrospectively in six patients with HER2-positive AGC, who underwent conversion surgery after trastuzumab-containing chemotherapy, and found that the 3-year survival rate was 66.7%. These findings imply that patients with HER2-positive AGC may be more suitable candidates for conversion surgery after trastuzumab-based chemotherapy, with greater improvements in prognosis, than those with HER2-negative AGC.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the feasibility and survival benefit of conversion surgery for patients who respond to chemotherapy plus trastuzumab should be urgently addressed (11). Some case reports have shown that trastuzumab has a beneficial effect on tumor regression, R0 resection rate, and long-term survival (12,13). Nevertheless, any role of trastuzumab played in the context of conversion surgery have not been reported on a larger scale.…”
Section: Introductionmentioning
confidence: 99%